PERAN MATA KULIAH KERJA PRAKTEK PADA TUGAS AKHIR MAHASISWA TEKNIK ARSITEKTUR DI JAKARTA - Kiki Maria (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2020)
Abstract Practical work is one of the requirements for taking the final project (thesis) in the Architectural Engineering Study Program. Practical Work Performed by students majoring in Architecture for approximately four (4) months to carry out activities on certain construction projects that are related to the field of architecture such as planning, implementation and supervision of institutions outside the campus in this case the Contractor or Planning Consultant. This research is to find out whether students in carrying out the Final Project also apply the experience gained while carrying out practical work. Based on the above background, we are very interested in proposing and trying to do research with the title "The Role of Practical Work Subjects in Engineering Student Program Final Project". This research was conducted in several stages, namely the survey stage, the data processing stage, and the conclusion drawing stage. In the survey stage, primary data collection is carried out by making a comparison between the Job Training Report and the Final Task Report. Comparisons were made at several universities which according to the plan would be chosen as sampling locations, namely: Bung Karno University, Pancasila University, Indonesian Christian University and "YAI" University. The second stage, data processing is done using the method of raising the sample, the method of analysis, and testing the hypothesis. The last stage was drawing conclusions about the Role of Practical Work Subjects in the Final Project of the Architectural Engineering Study Program.